The sulfur problem : cleaning up industrial feedstocks - Stirling, Diane (Royal Society of Chemistry, 2000)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. Sulfur compounds contaminate many industrially important feedstocks and, on release to the atmosphere as sulfur oxides, can cause widespread damage to the ecosystem. The main objectives of The Sulfur Problem: Cleaning Up Industrial Feedstocks are to demonstrate the importance of eliminating sulfur contaminants from the environment and the measures necessary to effect this. Using a systematic and pedagogical approach, the reader is first presented with the problem. Current technology for solving it is then outlined together with appropriate theory on the synthesis, structure and sorption behaviour of the materials used. Relevant characterisation techniques are described with reference to typical sorbents, to demonstrate how the sorption behaviour of the materials correlates with their properties. The book is unique in blending together aspects of environmental chemistry, materials/solid state chemistry, surface chemistry, catalysis and separation processes to address the problem of sulfur contaminants in a wide range of feedstocks.
Keywords: Sulfur compounds -- Decontamination.; Sulfur compounds -- Environmental aspects.; Feedstock -- Desulfurization.; elektronické knihy; electronic books